High-entropy alloy anti-fouling device and application

CN122916288APending Publication Date: 2026-10-16NORTHEASTERN UNIV CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611142954.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明旨在克服现有化学防垢法的污染问题、传统物理场装置的高能耗与复杂性、以及传统合金催化法的低效与短寿命缺陷

Benefits of technology

[0049] (1) High and stable scale prevention efficiency: Based on the built-in electric field network, the electrostatic catalytic effect is strong and uniform, which can efficiently induce the formation of aragonite scale, and the scale inhibition rate can reach more than 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916288A_ABST
    Figure CN122916288A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of the intersection of industrial water treatment, material science and corrosion prevention engineering, and particularly relates to a high-entropy alloy scale prevention device and application. The scale prevention device of the present application is placed in an outer sleeve pipeline, contains repeatedly arranged structural members made of high-entropy alloy, the high-entropy alloy is composed of elements with gradient electronegativity χ C > χ A > χ B > χ D , has a single face-centered cubic solid solution structure and a high-density micro-nano built-in electric field network, the inner wall of the pipeline is coated with an alloy coating, and a cyclone is arranged at the inlet. The scale prevention device of the present application can be used in various water scenes, does not require external energy input, and can realize physical scale prevention by itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the interdisciplinary technical field of industrial water treatment, materials science and corrosion prevention engineering, and specifically relates to a high-entropy alloy anti-scaling device and its application. Background Technology

[0002] In industrial circulating cooling water systems, boilers, heat exchangers, and seawater desalination processes, inorganic salt scaling (such as limescale, mainly composed of calcium carbonate, calcium sulfate, and silicates) is a common and costly problem. Calcium and magnesium ions in hard water combine with carbonate and sulfate ions to form precipitates that firmly adhere to the metal surfaces of equipment when temperatures rise, pressure changes, or pH values ​​shift. The scale layer has extremely low thermal conductivity, severely degrading heat transfer efficiency and leading to a significant increase in energy consumption. Simultaneously, it exacerbates the risk of under-deposit corrosion, reduces the flow cross-section, and increases flow resistance, ultimately forcing equipment shutdown for cleaning, resulting in substantial production losses and economic costs.

[0003] Traditional scale prevention methods mainly include chemical and physical methods. Chemical methods use scale inhibitors (such as phosphonates and polymers) to complex or disperse scale-forming ions, offering direct results but also incurring problems such as high operating costs, reagent residues, and potential eutrophication and secondary pollution. Physical methods attempt to alter the physicochemical state of water or scale-forming substances through an external physical field, achieving scale prevention and removal, and possessing environmental potential. Existing physical scale prevention technologies include magnetization, ultrasonic treatment, electrostatic field treatment, and electromagnetic field treatment. For example, electrostatic field treatment orients water molecules (dipoles) in an electric field, surrounding scale-forming ions, enhancing their solubility, and inhibiting scale formation. Electromagnetic field treatment uses a variable-frequency square wave signal to generate an alternating electromagnetic field, causing water molecule clusters to resonate and dissociate, promoting the formation of non-adhesive aragonite crystals from scale-forming ions. However, these physical field methods typically require continuous external energy input (such as electricity), have complex equipment, high installation and maintenance requirements, and their long-term effectiveness is often affected by factors such as water quality and flow rate.

[0004] Another physical method is alloy catalytic scale prevention, which utilizes a specific multi-element alloy to form a micro-galvanic cell in an electrolyte aqueous solution, generating a local micro-electric field that affects the crystallization process of scale-forming ions. However, existing technologies mostly use traditional copper-zinc based alloys (such as brass), whose design is based on experience, and whose microstructure is often multiphase with severe component segregation. This leads to three fundamental defects: (1) the generated micro-electric field is sparse, uneven, and unstable, resulting in limited scale prevention efficiency; (2) it is prone to "zinc de-corrosion" during use, with rapid loss of functional elements and short device life; and (3) the overall material performance is poor. Therefore, there is an urgent need to develop a scale prevention device based on a high-performance, long-life, and well-defined functional alloy to achieve efficient, environmentally friendly, and low-maintenance industrial scale prevention.

[0005] High-entropy alloys, as an emerging material design concept, provide a new platform for simultaneously solving the aforementioned problems. However, to successfully apply them to the field of scale prevention, two key scientific issues must be addressed: first, how to directionally design the alloy composition so that it can spontaneously generate a strong, uniform, and stable built-in catalytic electric field in water; and second, how to engineer this material into a reliable and easy-to-install industrial device. Summary of the Invention

[0006] This invention aims to overcome the pollution problems of existing chemical scale prevention methods, the high energy consumption and complexity of traditional physical field devices, and the inefficiency and short lifespan of traditional alloy catalysis methods. It provides a pipeline-type high-entropy alloy scale prevention device with a clear scale prevention mechanism, significant and long-lasting effect, no external energy required, environmentally friendly design, and applicability to various water systems, along with the design and preparation method of its core materials.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] The core innovation of this invention is that the functional components in the device that come into direct contact with the fluid are made of a high-entropy alloy designed in synergy with the "gradient electronegativity rule" and the "high-entropy single-phase rule".

[0009] The anti-scaling device is placed in the outer casing and contains repeating structural components made of high-entropy alloy, which can inhibit the formation of scale in the pipe. The shape of the structural components includes columnar, thin sheet with several holes, or spiral blade with several holes. The fluid flows in from the inlet end of the outer casing, passes through the anti-scaling device, and flows out from the outlet end.

[0010] A swirl vane can be installed at the inlet end of the outer casing pipe. Fluid flows into the pipe from the inlet end, generates swirl after passing through the swirl vane, and then flows through the anti-scaling device to the outlet end.

[0011] The anti-scaling device has one of the following three structures:

[0012] Structure 1: When the structural component is a circular plate made of high entropy alloy with several through holes, two circular plates are separated by an insulating spacer and combined to form a repeating unit. The insulating spacer has several through holes that match the holes of the circular plate to allow fluid to pass through. The repeating units are separated to form an anti-scaling device.

[0013] The outer edge of the disc can fit tightly with the inner wall of the outer sleeve pipe. Each repeating unit can be connected with bolts to fix the repeating unit and resist fluid impact. The through hole diameter is 4mm-30mm, the disc thickness is 5mm-20mm, and the repeating unit spacing is 10mm-100mm. The insulating spacer is made of polytetrafluoroethylene.

[0014] Structure 2: When the structural component is a cylinder made of high-entropy alloy, the two ends of the cylinder are covered with insulating diaphragms, which are combined to form a repeating unit. Each repeating unit is tightly connected to form an anti-scaling chain along the pipeline direction. Several anti-scaling chains constitute an anti-scaling device.

[0015] The two ends of the anti-scaling chain can be fixed by connecting plates. The outer edge of the connecting plate fits tightly with the inner wall of the outer sleeve pipe. Several holes are opened on the connecting plate for the cylinder to be inserted and fixed. The end face of the cylinder can be set as a spherical cap, with the bottom diameter of the spherical cap being larger than the diameter of the cylinder, so as to make the connection between the repeating units stable. The insulating spacer is made of polytetrafluoroethylene.

[0016] Structure 3: When the structural component is a spiral blade made of high-entropy alloy with several through holes, the spiral blade is a repeating unit. The spiral blade rotates along the spiral rod to form an anti-scaling device.

[0017] The spiral blades have an inclination angle of 15°-45°, a through hole diameter of 4mm-30mm, a spiral blade thickness of 5mm-20mm, and a spiral pitch of 10mm-100mm.

[0018] The anti-scaling device is made by an integrated molding process, and the whole is a continuous spiral structure. The central columnar spiral rod is the support body, and it is continuous from the center of rotation to the outer diameter of the spiral blades. Several through holes are opened on the spiral blades to allow fluid to pass through, so as to ensure uniform fluid distribution.

[0019] The continuous spiral blades with large-angle openings and uniform blade thickness reduce the lateral scouring of the tube bundle by the spiral flow, thus lowering the risk of vibration. At the same time, the continuous spiral shearing action helps to inhibit dirt deposition.

[0020] The inner wall of the outer pipe can be coated with an alloy coating, so that the inner wall of the pipe and the scale crystals carry the same charge, generating electrostatic repulsion and preventing scale crystals from adhering; the composition and content of the alloy coating are as follows: Cu 70at.%~95at.%, Ni 2at.%~25at.%, Co 1.0at.%~2.0at.%, P 0.5at.%~1.0at.%, rare earth element RE 0.1at.%~0.5at.%; wherein RE is selected from one or more of La, Ce, Pr, Nd, and Gd.

[0021] High-entropy alloys possess a single face-centered cubic solid solution structure, providing a high density of electrocatalytic active sites; internally, they have a high-density micro-nano-scale built-in electric field network, which polarizes the fluid medium and thus inhibits scale formation; the total configurational entropy of the alloy ΔS config >1.0R (R is the gas constant).

[0022] The elements in high-entropy alloys must meet the following requirements:

[0023] (1) Gradient electronegativity rule: The high-entropy alloy contains components A, B, C, and D, and the electronegativity χ of each component satisfies the gradient electronegativity rule: χ C > χ A > χ B > χ D Controlling the configurational entropy ΔS of high-entropy alloys config =-RΣ(x i lnx i x > 1.0R, where R is the gas constant and x i Let i be the mole fraction of component i;

[0024] Wherein: Component A is selected from one or more of the elements with electronegativity χ in the range of 1.85-1.95: Cu, Ni, and Co;

[0025] Component B is selected from one or more elements with electronegativity χ in the range of 1.55-1.65: Zn, Al, Mn;

[0026] Component C is selected from one or both of the elements with an electronegativity χ greater than 1.95: Sn and P;

[0027] Component D is selected from one or more of the following elements with an electronegativity χ less than 1.55: Mg, La, Ce, Er, and Y.

[0028] (2) Determine the atomic percentage (at.%) of each component so that the composition of the high-entropy alloy satisfies the general formula A. a B b C c D d Let a + b + c + d = 100%, where: the total content of component A, a, is 60 at.% - 80 at.%, the total content of component B, b, is 20 at.% - 30 at.%, the total content of component C, c, is 0 - 10 at.%, and the total content of component D, d, is 0 - 10 at.%; c and d can be 0 individually, but cannot be 0 simultaneously.

[0029] Furthermore, in component A, the content of Cu is 25 at.%-65 at.%, the content of Ni is 5 at.%-30 at.%, and the content of Co is 5 at.%-25 at.%; component C is Sn and / or P, with a total content of 0.5 at.%-5 at.%; and component D is Mg and / or Ce, with a total content of 0.5 at.%-5 at.%.

[0030] (3) High-entropy alloys may also contain other components: one or two of Ti and Bi; the total content of other components in high-entropy alloys is ≤5 at.).

[0031] High-entropy alloys are produced using a process combining pre-alloying and gradient melting, including the following:

[0032] (1) Pre-alloying: The volatile component Zn in component B and at least one of components C and D are mechanically alloyed with some high-melting-point component A metal powder to form pre-alloyed powder, and then cold-pressed into pre-alloyed billets.

[0033] (2) Gradient melting: Under the protection of inert gas, the remaining high melting point metal of component A is first melted to form a molten pool, and then the prepared pre-alloyed billet is added to the molten pool in batches under the protective atmosphere. At the same time, electromagnetic stirring is applied to achieve homogenization and obtain a melt with uniform composition.

[0034] (3) Forming and heat treatment: The melt is cast and solidified, and then the ingot is subjected to homogenization heat treatment at 1000℃-1100℃ for 2h-5h to obtain high entropy alloy (AHEA). The high entropy alloy has a single face-centered cubic solid solution structure and a high-density micro-nano-scale built-in electric field network.

[0035] The application of the high-entropy alloy anti-scaling device of the present invention includes the following: The anti-scaling device of the present invention can be used in various water scenarios such as circulating cooling water, boiler feedwater, central air conditioning, heat exchangers, and seawater desalination. It does not require external energy input and relies on the device itself to achieve physical anti-scaling, preventing calcium and magnesium ions in the water from forming precipitates with carbonate and sulfate ions and adhering to the equipment surface. The scale crystals are precipitated in the form of loose needle-like or clustered aragonite crystals and carried away by the water flow, avoiding the formation of dense calcite crystals to form a dense scale layer on the pipe wall.

[0036] This invention is a physical device that utilizes the electrochemical electrostatic catalytic function of high-performance multi-principal alloys (high-entropy alloys) to prevent inorganic scale deposition in water systems. The high-entropy alloy, prepared based on a rational design method of "gradient electronegativity synergistic high-entropy single phase," drives valence electrons to shift directionally from low-electrone components (B, D) to high-electrone components (A, C) by creating a gradient distribution of electronegativity among its components. This forms dynamic, localized charge density fluctuations within the crystal lattice, providing an intrinsic driving force for the generation of a built-in electric field. This alloy is then constructed into a suitable anti-scaling component for pipeline applications, providing long-term suppression of scale formation on the surfaces of heat exchangers, pipes, and other equipment.

[0037] By precisely controlling the atomic percentage (at.%) of each component, the total configuration entropy ΔS of the alloy is made possible. config >1.0R (R is the gas constant). The high entropy effect strongly inhibits the formation of brittle phases such as intermetallic compounds, driving the alloy to thermodynamically tend to form a single, homogeneous FCC solid solution phase. This ensures that the aforementioned built-in electric field network is distributed long-range, uniformly, and stably in the bulk phase of the material, fundamentally eliminating localized corrosion and functional degradation caused by compositional segregation.

[0038] Anti-scaling mechanism explanation: When water (a weak electrolyte) flows through the anti-scaling device (high-entropy alloy surface) of this invention, the high-density built-in electric field network within the alloy penetrates the interface, producing multiple synergistic effects on the water medium:

[0039] (1) Polarization and interference nucleation: The strong built-in electric field strongly polarizes water molecules and Ca in the water. 2+ Mg 2+ CO3 2- Plasma alters the hydration state and diffusion behavior of ions, interfering with the critical nucleation size and nucleation rate of scale crystals such as calcium carbonate.

[0040] (2) Induction of aragonite crystal formation: The electric field alters the kinetic path of CaCO3 crystallization, preferentially inducing its precipitation in the aragonite crystal form rather than the usually densely attached calcite crystal form. Aragonite crystals are loosely needle-like or clustered, and have weak adhesion to metal surfaces.

[0041] (3) Electrostatic repulsion: The stable electric field on the alloy surface may cause the formed micro-scale crystals or the metal surface of the equipment to be charged with the same charge, generating electrostatic repulsion and preventing them from further accumulating and adhering.

[0042] Ultimately, the macroscopic manifestation is that the scale precipitated from the water is mostly loose suspended particles that are carried away by the water flow and cannot form a hard, dense scale layer on the pipe wall or heat exchange surface.

[0043] Device structural design: This invention combines the aforementioned high-performance, high-entropy alloy material with three optimized tubular structures:

[0044] (1) Layered structure: It is composed of alternating layers of high-entropy alloy sheets and polytetrafluoroethylene insulating spacers, forming parallel narrow flow channels. This structure provides a huge effective catalytic surface area and enables the fluid to generate laminar or micro-turbulent flow, ensuring full contact between water and alloy.

[0045] (2) Columnar structure: It is composed of an array of multiple mutually insulated high-entropy alloy columns. The fluid flows around the columns, with a large contact area and complex flow pattern, which is conducive to the catalytic reaction.

[0046] (3) Spiral structure: It is composed of a high-entropy alloy spiral structure with multiple continuous spiral blades. The spiral blades are provided with multiple through holes to enhance the fluid turbulence characteristics, improve catalytic activity, and realize the physical scale inhibition function.

[0047] Both the sheet-type and columnar-type structures can be equipped with swirl vanes to pre-rotate the fluid entering the device, further enhancing mixing and contact. The inner wall of the device casing can also be coated with an alloy coating of specific components, providing additional corrosion protection and synergistic catalytic effects.

[0048] The present invention has the following beneficial effects:

[0049] (1) High and stable scale prevention efficiency: Based on the built-in electric field network, the electrostatic catalytic effect is strong and uniform, which can efficiently induce the formation of aragonite scale, and the scale inhibition rate can reach more than 90%.

[0050] (2) Ultra-long service life and maintenance-free: The high-entropy alloy does not contain lead, and the single FCC solid solution structure ensures extreme compositional uniformity and excellent resistance to selective corrosion. The device's function degrades very slowly during long-term operation, with a service life of up to several years and virtually maintenance-free.

[0051] (3) Zero energy consumption and environmental protection: The entire anti-scaling process relies entirely on the physical and chemical properties of the material itself, requiring no external power source or energy input, thus achieving zero operating energy consumption. At the same time, no chemical agents are added, and there are no pollutant emissions, making it environmentally friendly.

[0052] (4) Significant energy saving and consumption reduction: By effectively preventing the formation of scale and maintaining the high efficiency of heat transfer of heat exchange equipment, the system energy consumption can be significantly reduced.

[0053] (5) Integrated structure and function: The device has a simple and compact structure, which is easy to connect and install in existing pipelines. The core high-entropy alloy structural components have good strength and reliable operation.

[0054] (6) Easy installation and wide applicability: The device is designed with standard pipelines and can be quickly connected to existing systems via flanges, taking up almost no extra space. It is suitable for various water scenarios such as circulating cooling water, boiler feedwater, central air conditioning, hot water systems, and seawater desalination. Attached Figure Description

[0055] Figure 1 This is a schematic cross-sectional view of the layered high-entropy alloy anti-scaling device in Example 1 along the direction of water flow in the pipeline;

[0056] Figure 2 This is a schematic cross-sectional view along the pipe path of the layered high-entropy alloy anti-scaling device in Example 1;

[0057] Figure 3 This is a schematic cross-sectional view of the columnar high-entropy alloy anti-scaling device along the water flow direction in Example 2.

[0058] Figure 4 This is a schematic cross-sectional view of the columnar high-entropy alloy anti-scaling device along the pipe path in Example 2;

[0059] Figure 5 This is a schematic cross-sectional view of the spiral structure high-entropy alloy anti-scaling device along the water flow direction in Example 3;

[0060] Figure 6 This is a schematic cross-sectional view of the spiral structure high-entropy alloy anti-scaling device along the pipe path in Example 3;

[0061] Among them, 1-outer steel pipe, 2-inner wall alloy coating of pipeline, 3-structural component, 4-insulating partition, 5-connecting bolt, 6-swirl vane, 7-flange, 8-application scenario pipeline, 9-connecting plate. Detailed Implementation

[0062] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, all percentages are atomic percentages (at.%).

[0063] Example 1

[0064] Layered anti-scaling device.

[0065] like Figure 1 As shown, a pipeline-type high-entropy alloy sheet structure anti-scaling device comprises an outer steel pipe 1, an inner wall alloy coating 2, structural components 3 (high-entropy alloy porous discs) and insulating spacers 4 (PTFE insulating porous discs) stacked in alternating layers to form repeating units, connecting bolts 5 for fixing the repeating units, swirl vanes 6, and flanges 7. The aperture size of the high-entropy alloy porous discs and PTFE insulating porous discs is 4mm-9mm, depending on the actual water flow conditions. The materials of the outer steel pipe 1 and flanges 7 match the external application pipeline 8, typically carbon steel or stainless steel. Figure 2 This is a schematic diagram of the cross-sectional structure of the pipeline after assembly of a high-entropy alloy porous disc, a PTFE insulating porous disc, and connecting bolts.

[0066] The composition of the high-entropy alloy porous disc is as follows: Cu 45 at.%, Ni 15 at.%, Co 10 at.%, Zn 25.5 at.%, Sn 2 at.%, Mg 0.5 at.%, P 0.5 at.%, Ce 0.5 at.%, Ti 0.5 at.%, Bi 0.5 at.%. Its configurational entropy ΔS config The calculated value is approximately 1.58R.

[0067] The high-entropy alloy preparation method is as follows: First, Zn, Sn, Mg, Ce, P, and Bi powders are ball-milled with a portion of Cu powder to form a pre-alloyed billet; under argon protection, the remaining Cu, Ni, Co, and Ti are melted to form a molten pool, and then the pre-alloyed billet is added and electromagnetically stirred; after casting, the ingot is subjected to a homogenization heat treatment at 1050℃ for 4 hours. XRD analysis shows it to be a single FCC phase. The alloy coating composition on the inner wall of the outer steel pipe is: Cu 85 at.%, Ni 12.5 at.%, Co 1.5 at.%, P 0.8 at.%, Ce 0.2 at.%, prepared using a high-velocity oxygen fuel (HVOF) spraying process.

[0068] Water flows from the application scenario pipe 8, which has a swirl vane at one end, into the pipe equipped with the anti-scaling device. It first generates swirl through the swirl vane 6, and then flows through the multi-layer gap formed by the high-entropy alloy porous disc and the PTFE insulating porous disc, which are the anti-scaling functional components. It fully contacts the alloy surface and completes the anti-scaling treatment under the synergistic effect of the pipe-type layered structure anti-scaling device and the built-in electric field catalysis of the high-entropy alloy. Finally, it flows out of the device.

[0069] Example 2

[0070] Columnar structure anti-scaling device.

[0071] like Figure 3 As shown, a pipeline-type high-entropy alloy columnar anti-scaling device comprises an anti-scaling chain formed by alternating arrangements of an outer steel pipe 1, an inner wall alloy coating 2, structural components 3 (high-entropy alloy columns) and insulating spacers 4 (PTFE insulating rings), a swirl vane 6, a flange 7, and a connecting plate 9. The materials of the outer steel pipe 1 and the flange 7 are matched to the external application pipeline 8, typically carbon steel or stainless steel. The high-entropy alloy columns are separated by insulating rings to achieve mutual insulation. Figure 4 A schematic diagram of the cross-sectional structure of the pipeline after the anti-scalding chain and connecting disc are assembled.

[0072] The composition of the high-entropy alloy column is as follows: Cu 30 at.%, Ni 21.5 at.%, Co 15 at.%, Zn 30 at.%, Sn 2 at.%, Mg 0.5 at.%, Ce 0.5 at.%, P 0.5 at.%; its configuration entropy ΔS config >1.0R, the preparation process is the same as in Example 1. The composition and preparation process of the alloy coating on the inner wall of the pipeline are the same as in Example 1.

[0073] Water flows from the application scenario pipe 8, which has a swirl vane at one end, into the pipe equipped with the anti-scaling device. After passing through the swirl vane 6, it flows around the anti-scaling chain formed by multiple high-entropy alloy columns and finally flows out of the device. Under the synergistic effect of the pipe-type columnar structure anti-scaling device and the catalytic effect of the built-in electric field of the high-entropy alloy, the contact area is large and the anti-scaling effect is significant.

[0074] Example 3

[0075] Spiral structure anti-scaling device.

[0076] like Figure 5 As shown, a pipeline-type high-entropy alloy spiral structure anti-scaling device comprises an integrated high-entropy alloy spiral structure formed by rotating an outer steel pipe 1, an inner wall alloy coating 2, structural components 3 (high-entropy alloy porous spiral blades), and a flange 7. The materials of the outer steel pipe 1 and the flange 7 are matched to the external application pipeline 8, typically carbon steel or stainless steel. The composition of the inner wall alloy coating 2 is the same as in Example 1. Figure 6 This is a schematic diagram of the cross-sectional structure of a pipeline with an integrated high-entropy alloy continuous spiral structure with porous spiral blades, showing the direction of water flow.

[0077] The composition of the high-entropy alloy helical blade is as follows: Cu 40 at.%, Ni 20 at.%, Co 10 at.%, Zn 25 at.%, Sn 3.5 at.%, Mg 0.5 at.%, Ce 0.5 at.%, P 0.5 at.%; its configuration entropy ΔSconfig>1.0R, and the preparation process is the same as in Example 1. The composition and preparation process of the alloy coating on the inner wall of the pipeline are the same as in Example 1.

[0078] Water flows into the pipe equipped with the anti-scaling device from either end of the application scenario pipe 8, flows around multiple high-entropy alloy continuous spiral blades, forming a turbulent state, fully contacting the alloy surface, and achieving the scale inhibition function under the synergistic effect of the spiral structure anti-scaling device and the built-in electric field catalysis of the high-entropy alloy, and finally flows out of the device.

[0079] Performance verification:

[0080] The high-entropy alloy sheet prepared in Example 1 was processed into a test piece, and the scale inhibition test was performed in simulated hard water (4 mmol / L Ca2+). 2+ When immersed in 60℃ for 72 hours, its scale inhibition rate reached over 95%, and the precipitated scale was mainly loose aragonite. In long-term immersion tests of not less than 72 hours, its zinc ion dissolution was significantly lower than that of traditional Cu. 60 Zn 40 The alloy remains stable, indicating its excellent resistance to dezincification corrosion and long service life potential.

[0081] The anti-scaling devices described in Examples 1-3 were connected in series in a branch of a circulating cooling water system for field testing. After six months of continuous operation, only a very thin layer of soft scale was observed on the tube walls of the downstream heat exchanger, which could be easily dislodged by water hammer. In contrast, the heat exchangers in the parallel system without the device exhibited severe scaling, requiring regular chemical cleaning. This device required no maintenance throughout the entire testing period, demonstrating highly efficient and stable anti-scaling performance and an exceptionally long service life.

[0082] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-entropy alloy anti-scaling device, characterized in that, The anti-scaling device is placed in the outer casing of the pipeline and contains repeating structural components made of a high-entropy alloy. These components inhibit scale formation in the pipeline. The structural components can be columnar, thin sheets with several holes, or spiral blades with several holes. The high-entropy alloy has a single face-centered cubic solid solution structure and a built-in electric field network. It contains components A, B, C, and D, and the electronegativity χ of each component satisfies the gradient electronegativity rule: χ C > χ A > χ B > χ D .

2. The high-entropy alloy anti-scaling device according to claim 1, characterized in that, The anti-scaling device has one of the following three structures: Structure 1: When the structural component is a circular piece made of the high-entropy alloy with several through holes, two circular pieces are separated by an insulating spacer and combined to form a repeating unit. The insulating spacer has several through holes that match the holes in the circular piece to allow fluid to pass through. Each repeating unit is separated to form an anti-scaling device. Structure 2: When the structural component is a cylinder made of the high-entropy alloy, the two ends of the cylinder are covered with insulating diaphragms, which are combined to form repeating units. Each repeating unit is tightly connected to form an anti-scaling chain along the pipeline direction. Several anti-scaling chains constitute an anti-scaling device. Structure 3: When the structural component is a spiral blade with several through holes made of the high-entropy alloy, the spiral blade is a repeating unit. The spiral blade rotates along the spiral rod to form an anti-scaling device.

3. The high-entropy alloy anti-scaling device according to claim 2, characterized in that, A swirl vane is installed at the inlet end of the outer casing pipe. Fluid flows into the pipe from the inlet end, and after passing through the swirl vane to generate swirl, it flows through the anti-scaling device to the outlet end. In the first structure: the outer edge of the disc fits tightly with the inner wall of the outer sleeve, and each repeating unit is connected and fixed with bolts; the diameter of the through hole is 4mm-30mm, the thickness of the disc is 5mm-20mm, and the spacing between the repeating units is 10mm-100mm; In the second structure: the two ends of the anti-scaling chain are fixed by connecting plates. The outer edge of the connecting plate is tightly fitted with the inner wall of the outer sleeve pipe. Several holes are opened on the connecting plate for the cylinder to be inserted and fixed. The end face of the cylinder is set as a spherical cap, and the diameter of the bottom surface of the spherical cap is greater than the diameter of the cylinder. In the third structure: the outer edge of the spiral blade fits tightly with the inner wall of the outer sleeve; the inclination angle of the spiral blade is 15°-45°, the diameter of the through hole is 4mm-30mm, the thickness of the spiral blade is 5mm-20mm, and the spiral pitch is 10mm-100mm.

4. The high-entropy alloy anti-scaling device according to claim 1, characterized in that, The inner wall of the outer casing is coated with an alloy coating, which makes the inner wall of the casing and the scale carry the same charge, generating electrostatic repulsion and preventing scale adhesion. The composition and content of the alloy coating are as follows: Cu 70at.%~95at.%, Ni 2at.%~25at.%, Co 1.0at.%~2.0at.%, P 0.5at.%~1.0at.%, rare earth element RE 0.1at.%~0.5at.%; wherein, RE is selected from one or more of La, Ce, Pr, Nd, and Gd.

5. The high-entropy alloy anti-scaling device according to claim 1, characterized in that, Component A is selected from elements with electronegativity χ in the range of 1.85-1.95, component B is selected from elements with electronegativity χ in the range of 1.55-1.65, component C is selected from elements with electronegativity χ greater than 1.95, and component D is selected from elements with electronegativity χ less than 1.

55.

6. The high-entropy alloy anti-scaling device according to claim 5, characterized in that, Component A is selected from one or more of Cu, Ni, and Co; Component B is selected from one or more of Zn, Al, and Mn; Component C is selected from one or two of Sn and P; Component D is selected from one or more of Mg, La, Ce, Er, and Y.

7. The high-entropy alloy anti-scaling device according to claim 5, characterized in that, The high-entropy alloy is composed of the general formula A. a B b C c D d Let a + b + c + d = 100%, where: the total content of component A, a, is 60 at.% - 80 at.%, the total content of component B, b, is 20 at.% - 30 at.%, the total content of component C, c, is 0 - 10 at.%, and the total content of component D, d, is 0 - 10 at.%; c and d are not both 0.

8. A high-entropy alloy anti-scaling device according to claim 7, characterized in that, In component A, Cu content is 25 at.%-65 at.%, Ni content is 5 at.%-30 at.%, and Co content is 5 at.%-25 at.%; component C is one or both of Sn and P, with a total content of 0.5 at.%-5 at.%; component D is one or both of Mg and Ce, with a total content of 0.5 at.%-5 at.%. The high-entropy alloy also contains one or both of Ti and Bi, and the total content of the two in the high-entropy alloy is ≤5 at.

9. A high-entropy alloy anti-scaling device according to claim 1, characterized in that, The high-entropy alloy is prepared using a process combining pre-alloying and gradient melting, and the preparation method includes the following: (1) Pre-alloying: The volatile components in component B and at least one of components C and D are mechanically alloyed with a portion of component A metal powder to form pre-alloyed powder, which is then cold-pressed into pre-alloyed billets. (2) Gradient melting: Under the protection of inert gas, the remaining A component metal is first melted to form a molten pool, and then the prepared pre-alloyed billet is added to the molten pool in batches under the protective atmosphere to obtain a melt with uniform composition. (3) Forming and heat treatment: The melt is cast and solidified into an ingot, and homogenized at 1000℃-1100℃ for 2h-5h to obtain a high-entropy alloy with a single face-centered cubic solid solution structure and a high-density micro-nano-scale built-in electric field network.

10. The application of the high-entropy alloy anti-scaling device according to claim 1, characterized in that, The scale prevention device is used in water scenarios including circulating cooling water, boiler feedwater, central air conditioning, heat exchangers, and seawater desalination. It does not require external energy input and relies on the device itself to achieve physical scale prevention, so that scale crystals precipitate out in loose needle-like or clustered aragonite crystal form and are carried away by the water flow, avoiding the formation of dense calcite crystal form and dense scale layer on the pipe wall.